2011
DOI: 10.1016/j.bpj.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Unlinking of Supercoiled DNA Catenanes by Type IIA Topoisomerases

Abstract: It was found recently that DNA catenanes, formed during replication of circular plasmids, become positively (+) supercoiled, and the unlinking of such catenanes by type IIA topoisomerases proceeds much more efficiently than the unlinking of negatively (-) supercoiled catenanes. In an attempt to explain this striking finding we studied, by computer simulation, conformational properties of supercoiled DNA catenanes. Although the simulation showed that conformational properties of (+) and (-) supercoiled replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Although efficient resolution of cen-UFBs is mediated primarily by TOP2A, it is facilitated by PICH and TOP3A (96,132). Since the decatenation activity of TOP2 has been proposed to be most efficient on positively supercoiled catenanes, there is the intriguing possibility that PICH and TOP3A catalyze positive supercoiling in order to facilitate the rapid decatenation of cen-UFBs through stimulation of TOP2A (135)(136)(137). In this context and by analogy with the function of prokaryotic Reverse-gyrases critical to protect DNA against thermal denaturation (38,97,138), the positive supercoiling activity of the PICH-TOP3A complex might also contribute to protecting DNA against denaturation when exposed to mitotic spindle forces (139).…”
Section: Roles Of Top3a At Ultra-fine Anaphase Bridgesmentioning
confidence: 99%
“…Although efficient resolution of cen-UFBs is mediated primarily by TOP2A, it is facilitated by PICH and TOP3A (96,132). Since the decatenation activity of TOP2 has been proposed to be most efficient on positively supercoiled catenanes, there is the intriguing possibility that PICH and TOP3A catalyze positive supercoiling in order to facilitate the rapid decatenation of cen-UFBs through stimulation of TOP2A (135)(136)(137). In this context and by analogy with the function of prokaryotic Reverse-gyrases critical to protect DNA against thermal denaturation (38,97,138), the positive supercoiling activity of the PICH-TOP3A complex might also contribute to protecting DNA against denaturation when exposed to mitotic spindle forces (139).…”
Section: Roles Of Top3a At Ultra-fine Anaphase Bridgesmentioning
confidence: 99%
“…Understanding the interplay between supercoiling and pre-catenation in partially replicated molecules is hindered, though, by the fact that DNA conformation is disturbed during sample preparation. On the other hand, several studies convincingly proved that computer simulation can give a very accurate description of the DNA properties that are difficult to address experimentally (Martinez-Robles et al, 2009;Rawdon et al, 2016;Vologodskii, 2011;Vologodskii and Rybenkov, 2009;Vologodskii and Cozzarelli, 1993;Witz and Stasiak, 2010). For all these reasons, here we used the worm-like chain (WLC) model in combination with Metropolis Monte Carlo (MC) numerical simulation to study the dynamics of DNA topology in partially replicated plasmid DNA molecules, once these RIs are isolated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, in Saccharomyces cerevisiae , fully replicated catenanes were found to be transiently positively supercoiled (Figure 9B) during mitosis (76). Computer simulations showed that positive supercoiling of individual DNA circles in catenanes with right-handed crossings makes these catenanes more likely to undergo decatenation by type II DNA topoisomerases as compared to right-handed catenanes composed of negative supercoiled DNA circles (98).…”
Section: Introductionmentioning
confidence: 99%